2014
DOI: 10.1021/jp412572e
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Methane Adsorption in Porous Aromatic Frameworks: An FTIR, Raman, and Theoretical Combined Study

Abstract: We present a vibrational study of PAF-302, belonging to the class of porous aromatic frameworks (PAFs), recently synthesized and applied in several applications involving gas adsorption. The precursor, tetrakis(4-bromophenyl) methane (TBPM), and the polymer were studied with FTIR and Raman spectroscopies to investigate the structure of PAF-302, whereas the system after methane adsorption was studied by FTIR, also varying the CH 4 loading, to get some hints on the strength of the interactions with adsorbed meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
3
18
0
Order By: Relevance
“…The characteristic Raman shifts of the C−D stretching modes (1800−2500 cm −1 ) are distinctly different from the C−H stretching modes (2800−3000 cm −1 ). 51 Similar satellite peaks were observed (Figure S11), providing additional strong support for our interpretation. The proposed reaction mechanism that governs the formation of CH 3 −O−Ti is illustrated in the top panel of Next, we conducted in operando ATR−FTIR measurements to probe the reaction intermediates in the subsequent oxidation steps.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The characteristic Raman shifts of the C−D stretching modes (1800−2500 cm −1 ) are distinctly different from the C−H stretching modes (2800−3000 cm −1 ). 51 Similar satellite peaks were observed (Figure S11), providing additional strong support for our interpretation. The proposed reaction mechanism that governs the formation of CH 3 −O−Ti is illustrated in the top panel of Next, we conducted in operando ATR−FTIR measurements to probe the reaction intermediates in the subsequent oxidation steps.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
“…To rule out the possibility that these two satellite peaks are due to impurities, we performed Raman characterization using isotope-labeled methane (CD 4 ). The characteristic Raman shifts of the C–D stretching modes (1800–2500 cm –1 ) are distinctly different from the C–H stretching modes (2800–3000 cm –1 ) . Similar satellite peaks were observed (Figure S11), providing additional strong support for our interpretation.…”
Section: Resultssupporting
confidence: 83%
“…The main absorptions in the ranges of 800-1100, 1300-1800, 2800-3100, and 3600-3800 cm À1 are the characteristic vibration/stretching frequencies of aromatic structures, oxygen-containing functional groups, aliphatic structures, and the intermolecular H-bonding, respectively. [24][25][26][27] These results clearly indicate that the composition of AS is a mixture of different organic and inorganic components and have intricate intermolecular interactions. The structure of AS is further studied by XRD, and the result is shown in Figure 2(b).…”
Section: As Propertiesmentioning
confidence: 99%
“…Molecular simulation studies, using grand-canonical Monte Carlo, were also applied to PAFs structures by introducing polar organic groups to biphenyl builder units with the objective to investigate their adsorption and separating ability toward methane, CO 2 and other noble gases such as Xenon, thanks to the strong interaction established between adsorbed molecules and organic linkers [114,115]. Between the simulated functional PAFs-type materials, it was found that tetrahydrofuran-like ether-functionalized PAF-1 exhibited higher adsorption capacity for CO 2 at 1 bar and 298 K (10 mol per kg of adsorbent) and also higher [116,117,118].…”
Section: Pafs: Adsorption Storage and Gas Uptake Applicationsmentioning
confidence: 99%